2011
DOI: 10.2174/187152511798120949
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Oxidative Stress Related Genes and New Antioxidant Therapy in Diabetic Nephropathy

Abstract: A genetic component of diabetes and its complications (including diabetic nephropathy (DN)) is obvious, but the causative genes and mechanisms have not yet been satisfactorily identified. Oxidative stress is a single mechanism relating all major pathways responsible for diabetic damage. Numerous oxidative stress-related genes are positional candidates (determined by GWAS) and candidate genes studies confirm the association of their polymorphisms with DN. We present here their overview and connection to the "ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Various mechanisms are involved in the adaptive cellular responses which include functional chaperons, antioxidant production and regulation of cellular signals for protein synthesis to survive under oxidative stress conditions [9]. Numerous oxidative stress-related genes are positional candidates, determined by genome-wide association studies (GWAS) and candidate genes studies have confirmed the association of their SNPs with DN [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms are involved in the adaptive cellular responses which include functional chaperons, antioxidant production and regulation of cellular signals for protein synthesis to survive under oxidative stress conditions [9]. Numerous oxidative stress-related genes are positional candidates, determined by genome-wide association studies (GWAS) and candidate genes studies have confirmed the association of their SNPs with DN [10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of interindividual variability in the development of diabetic nephropathy (DN), despite similar levels of glycemic control and clustering of DN within families, suggests there are additional risk factors, including genetic predisposition (2). Because reactive oxygen species (ROS) are also implicated (3), polymorphic genetic loci encoding variants in proteins, which may protect against ROS, may be of importance. Haptoglobin (HP) (http://www.ncbi.nlm.nih.gov/gene/3240, 16q22.2), an abundant serum protein whose primary function is to protect against the pro-oxidative activity of extracorpuscular hemoglobin (Hb), is one potential determinant of susceptibility to DN (4).…”
mentioning
confidence: 99%
“…The interindividual variability in the risk for developing DN and its clustering within families suggest a substantial genetic predisposition [2,3]. As reactive oxygen species, particularly those derived from iron, have been implicated in the progression of DN and other vascular complications of Diabetes, polymorphic genetic loci encoding variants in enzymes protecting against iron-induced oxidative stress serve as potential susceptibility determinants for the development of DN [4–7]. …”
mentioning
confidence: 99%